2018
DOI: 10.1016/j.celrep.2018.06.053
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of Conditioned Taste Aversion in Cortico-Amygdala Circuits

Abstract: Avoidance of potentially toxic food by means of conditioned taste aversion is critical for survival of many animals. However, the underlying neuronal mechanisms are poorly understood. Here, using two-photon calcium imaging of defined gustatory cortex neurons in vivo, we show that conditioned taste aversion dynamically shifts neuronal population coding by stimulus-specific recruitment of neurons that project to the basolateral amygdala.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
84
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 33 publications
12
84
1
Order By: Relevance
“…Some forms of taste learning, such as social transmission of food preferences (Bunsey and Eichenbaum, 1995;Countryman et al, 2005), are considered to be hippocampal dependent; other paradigms (e.g., conditioned taste aversion) undergo variable effects after hippocampal lesions (Yamamoto et al, 1995;Stone et al, 2005;Chinnakkaruppan et al, 2014). Future studies in which individual neurons are recorded during taste learning, which have been informative when focused on other nodes of the taste system (Grossman et al, 2008;Lavi et al, 2018), may help to decipher how the hippocampus encodes tastes and contexts to guide future food choices.…”
Section: Discussionmentioning
confidence: 99%
“…Some forms of taste learning, such as social transmission of food preferences (Bunsey and Eichenbaum, 1995;Countryman et al, 2005), are considered to be hippocampal dependent; other paradigms (e.g., conditioned taste aversion) undergo variable effects after hippocampal lesions (Yamamoto et al, 1995;Stone et al, 2005;Chinnakkaruppan et al, 2014). Future studies in which individual neurons are recorded during taste learning, which have been informative when focused on other nodes of the taste system (Grossman et al, 2008;Lavi et al, 2018), may help to decipher how the hippocampus encodes tastes and contexts to guide future food choices.…”
Section: Discussionmentioning
confidence: 99%
“…Rodent studies further demonstrated roles for the IC in multisensory (Gogolla, Takesian, Feng, Fagiolini, & Hensch, 2014; Rodgers, Benison, Klein, & Barth, 2008) and pain processing (Tan et al, 2017), representation of valence (Wang et al, 2018), learning and memory (Bermúdez-Rattoni, Okuda, Roozendaal, & McGaugh, 2005; Lavi, Jacobson, Rosenblum, & Lüthi, 2018), social interactions (Rogers-Carter et al, 2018), gustation (Peng et al, 2015; Wang et al, 2018), drug cravings and malaise (Contreras, Ceric, & Torrealba, 2007), and aversive states such as hunger, thirst, and anxiety (Gehrlach et al, 2019; Livneh et al, 2017, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Relatively less work has been done in mice, an animal model that offers easier access to genetic tools to manipulate and visualize neuronal activity. Although a considerable amount of studies have investigated either spatial features of cortical taste-evoked activity in-vivo (Chen et al 2011;Fletcher et al 2017;Lavi et al 2018;Livneh et al 2017) or taste behavior (Graham et al 2014;Peng et al 2015), limited information is available on cortical taste electrophysiology in awake mice. One recent study described how GC neurons encoded gustatory information when taste stimuli were injected into the mouths of alert mice via intraoral cannulas (IOCs) (Levitan et al 2019).…”
Section: Introductionmentioning
confidence: 99%